2014
DOI: 10.1161/jaha.114.000857
|View full text |Cite
|
Sign up to set email alerts
|

Postextrasystolic Blood Pressure Potentiation Predicts Poor Outcome of Cardiac Patients

Abstract: BackgroundPostextrasystolic blood pressure potentiation (PESP), the pulse wave augmentation after an extrasystolic beat, is typically enhanced in heart failure (HF) patients. This study prospectively tested the association of PESP and mortality in cardiac patients.Methods and ResultsConsecutive patients (n=941; mean age, 61 years; 19% female) presenting with acute myocardial infarction were enrolled between May 2000 and March 2005 and followed up until August 2010. The main study outcome was 5‐year all‐cause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…P 1 /P 2-10 ) at admission were >1.03 in both patients, meaning that both patients would be classified as 'PESP present' according to the definition used in the post-MI study described above. 14 In one of the patients (Patient 1), PESP numerical ratio at discharge decreased to 0.98, re-classifying the patient as 'PESP absent' at this time point. Concomitantly, the NT-proBNP plasma level was also lower at discharge than at admission.…”
Section: Future Directionsmentioning
confidence: 93%
See 2 more Smart Citations
“…P 1 /P 2-10 ) at admission were >1.03 in both patients, meaning that both patients would be classified as 'PESP present' according to the definition used in the post-MI study described above. 14 In one of the patients (Patient 1), PESP numerical ratio at discharge decreased to 0.98, re-classifying the patient as 'PESP absent' at this time point. Concomitantly, the NT-proBNP plasma level was also lower at discharge than at admission.…”
Section: Future Directionsmentioning
confidence: 93%
“…14 To establish a new, simply applicable, non-invasive risk predictor, we decided to investigate PESP at the blood pressure level using non-invasive measurements. On days 5-9 after MI, patients underwent a 30-minute recording of ECG and blood pressure.…”
Section: Post-extrasystolic Potentiation As a Risk Predictor In Cardimentioning
confidence: 99%
See 1 more Smart Citation
“…During the screening period of the Autonomic Regulation Trial (ART) [5], we identified 32 patients suffering from acute myocardial infarction (MI) who were excluded from the ART study analyses because of AF [5]. These patients comprised the study cohort of the present analysis.…”
Section: Study Cohortmentioning
confidence: 99%
“…This phenomenon is termed post-extrasystolic potentiation (PESP) [3,4]. Recently, we reported that PESP, measured at the blood pressure level, is a powerful and independent predictor of mortality in survivors of myocardial infarction (MI) [5].…”
Section: Introductionmentioning
confidence: 99%